Analisis Kinerja Keuangan Pemerintah Kota Probolinggo Guna Mengoptimalkan Kekayaan Daerah - Mustagis, Lailatul Fitriah Giyasul; ., Andriana; ., Kartika; Kurrohman, Taufik; Wasito, Wasito (Study Program of Management Faculty of Economics and Business University of Jember, 2024)
This study aims to analyze the financial performance of the Probolinggo City Government in 2018-2022, analyze the obstacles faced and efforts that can be made to optimize PAD. This study uses a qualitative case study approach. The location of the study is the BPPKAD of Probolinggo City. The data used are the 2018-2022 financial reports and interviews with employees and heads of revenue. The results of the study show that in 2019 and 2022 the target was not achieved. The average degree of fiscal decentralization is in the low category, the dependency ratio is very high, the independence ratio is instructive, and the effectiveness ratio is in the effective category. In addition, the obstacles faced are the lack of taxpayer awareness, less than optimal employee performance, lack of coordination with other agencies, the implementation of the HKPD Law, geographical conditions, many competitors, technological sophistication, and uncertainty of asset sales, as well as uneven data collection. Some of the efforts made include; conducting education, following taxpayer patterns, employee evaluation, digitizing payments, revitalizing and reallocating, holding events, collaborating with several parties, and evenly collecting data, as well as installing tax recording devices. Keywords: Financial Performance, PAD, Ratios, Obstacles, Efforts